VD_FINDINFO AA 1/12 - 53/12 vom 24. Mai 2012 - VD Tribunal cantonal (2012)
ACCIDENT, SÉQUELLE TARDIVE, LIEN DE CAUSALITÉ, MESURE D'INSTRUCTIONASSURANCE SOCIALE, EXPERTISE | 6 al. 1 LAA, 44 LPGA, 11 OLAA